2007
DOI: 10.1007/s00468-007-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in photosynthesis in six woody species with different leaf phenology in a valley savanna in southwestern China

Abstract: During 2003During -2005, we examined the effect of seasonal drought on water status, gas exchange, d 13 C, chlorophyll fluorescence and spectral reflectance in six woody species in a valley savanna near the Yuanjiang River (the upper Red River) in southwestern China. Three different phenological types of these woody species were compared, i.e., an evergreen species, Cyclobalanopsis helferiana, two winter-deciduous (WD) species, Buchanania latifolia and Symplocos racemosa, and three droughtdeciduous (DD) speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 62 publications
4
34
0
4
Order By: Relevance
“…For gc of the sample tree species at the SAF site, we used the gc values from the literature (Zhang et al 2007) for the same site.…”
Section: Tc-ta Variations In a Changing Climatementioning
confidence: 99%
“…For gc of the sample tree species at the SAF site, we used the gc values from the literature (Zhang et al 2007) for the same site.…”
Section: Tc-ta Variations In a Changing Climatementioning
confidence: 99%
“…The frequent temporary water deficit caused by the fluctuation of soil water is considered one of the major limiting factors in survival, growth and distribution of plant species and the competition among species in the karst vegetation. A large number of studies on morphological and physiological adaptive responses of the karst plants to water deficit have been focused on woody species or species grown under controlled environments (Chen et al, 2009;Deng et al, 2006;Liu et al, 2010Liu et al, , 2011aWei et al, 2007;Wu et al, 2009;Zhang et al, 2007;Zhu et al, 2009). Only few comparative field studies have been reported for the purpose of 'site-species matching', which can provide valuable suggestions on selecting species candidates for specific restoration sites.…”
Section: Introductionmentioning
confidence: 98%
“…For example, soil water content ranges from 2.2 to 15.0% by weight from one microhabitat to another (Zhang et al 2006). Previous studies on morphological and physiological adaptations of karst plants to water stress have focused mainly on the responses of plants to homogeneous water conditions (Zhang et al 2007;Chen et al 2009;Wu et al 2009;Zhu et al 2009). The responses of karst plants to heterogeneous water resources have yet to be studied.…”
Section: Introductionmentioning
confidence: 99%